Repellent activity of common spices against the rice weevil, Sitophilus zeamais Motsch (Coleoptera, Curculionidae) - Ishii, Takahiro; Matsuzawa, Haruo; Vairappan, Charles Santhanaraju (Journal of Tropical Biology & Conservation (JTBC), 2016)
Five essential oils and eight extracts of common spices were screened and evaluated for repellent activity against adults of the rice weevil, Sitophilus zeamais (Motsch.), using the modified filter paper impregnation method. Both extracts of cinnamon (Cinnamomum zeylanicum) and essential oils of gingers, Etlingera elatior, E. pyramidosphaera and Zingiber officinale, showed strong repellent activity against S. zeamis at 20 mg/ml. Cinnamon methanol extract exhibited potent repellent activity at the concentration of 10 mg/ml. Extracts of turmeric (Curcuma longa) and black pepper (Piper nigrum) showed moderate repellent activity at 20 or 50 mg/ml. However, extracts of lemongrass (Cymbopogon citratus) and dry chili (Capsicum annuum) exhibited weak attractant activity. The findings from this research demonstrate the possible use of these spices as repellent of rice weevil in stored products.